The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5303/jkas.2017.50.3.41
|View full text |Cite
|
Sign up to set email alerts
|

Photometric Study of Npa Rotator (5247) Krylov

Abstract: Abstract:We conduct BVRI and R band photometric observations of asteroid (5247) Krylov from January 2016 to April 2016 for 51 nights using the Korea Microlensing Telescope Network (KMTNet). The color indices of (5247) Krylov at the light curve maxima are determined as B − V = 0.841 ± 0.035, V − R = 0.418 ± 0.031, and V − I = 0.871 ± 0.031 where the phase angle is 14.1• . They are acquired after the standardization of BVRI instrumental measurements using the ensemble normalization technique. Based on the color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…NPA rotation of Krylov was first reported by Pravec et al (2006). Following this, Lee et al (2017) confirmed NPA rotation of Krylov based on its double-period light curve (P 1 = 82.188 hr, P 2 = 67.13 hr), and they classified the taxonomy of this asteroid as the S-type. In addition, the diameter of Krylov has been estimated independently by infrared observations of satellites AKARI and NEO-WISE: however, the AKARI diameter (10.44 ± 0.37 km; Usui et al 2011) does not match well with the NEOWISE diameters (7.716 ± 0.043 or 8.665 ± 0.557 km; Mainzer et al 2019).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…NPA rotation of Krylov was first reported by Pravec et al (2006). Following this, Lee et al (2017) confirmed NPA rotation of Krylov based on its double-period light curve (P 1 = 82.188 hr, P 2 = 67.13 hr), and they classified the taxonomy of this asteroid as the S-type. In addition, the diameter of Krylov has been estimated independently by infrared observations of satellites AKARI and NEO-WISE: however, the AKARI diameter (10.44 ± 0.37 km; Usui et al 2011) does not match well with the NEOWISE diameters (7.716 ± 0.043 or 8.665 ± 0.557 km; Mainzer et al 2019).…”
Section: Introductionmentioning
confidence: 72%
“…1 shows a part of the 2017 light curves. In addition, a part of the 2016 light curves by Lee et al (2017) was reproduced in the third panel of Fig. 1.…”
Section: Disk-integrated Photometrymentioning
confidence: 97%
See 2 more Smart Citations
“…Apparently, our principal-axis-rotation model is good enough given the quality and coverage of the data to fit the main period in light curves of some tumblers. For example, our principal-axis-rotation model of (5247) Krylov has the rotation period of 82.291 h, which is the most prominent period of its light curves given by a combination of two physical periods of free precession: 1/82.291 ≈ 1/68.15 h − 1/396.30 h (Lee et al 2017(Lee et al , 2018.…”
Section: New Spin and Shape Modelsmentioning
confidence: 99%